Konsep Ajaran Iman Tentang Maria Sebagai Bunda Allah (Theotokos) Menurut Telaah Aidan Nichols - Ranubaya, Fransesco Agnes; Situmorang, Markus (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2024)
Mother Mary is an example of the Catholic Church in terms of faith, love and perfect union with Christ. Mother Mary is a perfect example of reflecting Christ. Mary is the best example for the Church, because the Church is also called as Mother and virgin, and as the bride of Christ. The Church Fathers linked Mary's role as Mother of God to her role as the new Eve. Mother Mary gave birth to the Lord Jesus who became the savior of humans from the sins inherited from Eve's sins. The writing of this scientific work uses the critical analysis method through an approach study of documents based on Aidan Nichols' research. This research provides several conclusions, including that the dogma of Mary as the Mother of God (Theotokos) through the Holy Spirit of Mary, the virgin, received in her womb Jesus Christ, the Son of God, who is one being with the Father, and gave Him to the world so that the Catholic Church calls Mary as Mother of God. The dogmas regarding the Virgin Mary taught by the Catholic Church include the teachings regarding Mary who died temporarily (a temporal death/sententia communior), Mary being assumed body and soul into heaven (De fide), Mary the Mother of God (Theotokos), Mary is the Mediatrix/ Mediator of all graces, with her intercession in Heaven (Mediatio in speciali), Mary is honored in heaven as Queen of the universe, and the teaching about Mary is the Mother of the Church, the Mother of the faithful. A critical analysis of the concept of faith teachings about Mary as the Mother of God (Theotokos) according to Aidan Nichols' study is that all the graces in Mary, expressed biblically as narratives that need to be known and told because they can build Mary's meaning in the divine plan, are the full implementation of her role and sovereign as the Mother of the Word incarnate.